Abnormal dynamic functional connectivity in first‐episode, drug‐naïve adolescents with major depressive disorder. Issue 7 (7th April 2022) - Zheng, Ruiping; Chen, Yuan; Jiang, Yu; Zhou, Bingqian; Li, Shuying; Wei, Yarui; Wang, Caihong; Han, Shaoqiang; Zhang, Yong; Cheng, Jingliang
Abstract: Previous neuroimaging studies have identified disrupted large‐scale functional brain networks in major depressive disorder (MDD); however, most of them focused on adult patients and were based on static functional connectivity (FC). Thus, we aimed to investigate the patterns of change in dynamic FC in depressed adolescents. Resting‐state functional magnetic resonance imaging data were acquired from 60 first‐episode, drug‐naïve adolescents with MDD and 60 matched healthy controls (HCs). Then, the dynamic FC properties were analyzed using a sliding windows approach, k ‐means clustering, and graph theory methods. The intrinsic brain FC were clustered into two configuration states—a more frequent and relatively sparsely connected State 1 and a less frequent and more strongly interconnected State 2. Compared with HCs, depressed adolescents had higher reoccurrence fraction and dwell time in State 1, and lower reoccurrence fraction and dwell time in State 2, and higher total number of transitions between the two states. Depressed adolescents showed decreased FC within the default mode network (DMN) and between the DMN and other networks in State 1. Additionally, the MDD group showed higher variances in the global and local efficiency. Furthermore, the duration of illness was positively correlated with the number of state transitions, and the 17‐item Hamilton Depression Rating Scale score was positively correlated with the mean dwell time in State 1. This study demonstrated abnormal dynamic FC in depressed adolescents, which provided new insights into the pathophysiological mechanisms of adolescent‐onset depression. Abstract : This dynamic functional connectivity (FC) study suggests that adolescent depression is characterized by unstable network dynamic pattern, altered state transition metrics, and disrupted FC in a weakly connected state. Furthermore, mean dwell time in this weakly connected state is associated with disease severity.